Synovial osteochondromatosis associated with osteoarthrits causing ulnar nerve palsy - Weerasuriya, Thisara (BMJ Publishing Group, 2011)
Synovial oteochondromatosis has been described in the knee joint commonly but this case was in the elbow and was associated with ulnar nerve palsy. Generally it has been the belief that synovial osteochondromatosis is not associated with ostearthritis of the joint but, in this case it was clearly associated with osteoarthritis of the elbow. Therefore the authors wish to report this case of a rare condition with an unusual association.